2021
DOI: 10.3389/fcvm.2021.633611
|View full text |Cite
|
Sign up to set email alerts
|

Cinematic Rendering in Mixed-Reality Holograms: A New 3D Preoperative Planning Tool in Pediatric Heart Surgery

Abstract: Cinematic rendering (CR) is based on a new algorithm that creates a photo-realistic three-dimensional (3D) picture from cross-sectional images. Previous studies have shown its positive impact on preoperative planning. To date, CR presentation has only been possible on 2D screens which limited natural 3D perception. To depict CR-hearts spatially, we used mixed-reality technology and mapped corresponding hearts as holograms in 3D space. Our aim was to assess the benefits of CR-holograms in the preoperative plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 30 publications
(20 reference statements)
1
29
0
2
Order By: Relevance
“…A recent study by Gehrsitz et al has demonstrated the usefulness of MR in the pre-operative planning of pediatric heart surgeries. The use of MR was found to significantly improve the depth perception and portrayal of the pathology when compared to the two-dimensional (2D) medical images and 3DPHM [ 21 ]. The use of AR has also been shown constructive in Valve-in-Valve Transcatheter Heart Valve Implantation and percutaneous coronary intervention procedures [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study by Gehrsitz et al has demonstrated the usefulness of MR in the pre-operative planning of pediatric heart surgeries. The use of MR was found to significantly improve the depth perception and portrayal of the pathology when compared to the two-dimensional (2D) medical images and 3DPHM [ 21 ]. The use of AR has also been shown constructive in Valve-in-Valve Transcatheter Heart Valve Implantation and percutaneous coronary intervention procedures [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially for MR, its superiority over the current visualization technique requires further validation. The published article to compare 3D printing and MR in pediatric heart surgeries is limited to one surgeon’s assessment based on a single-center experience [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current clinical applications include minimally invasive cardiac procedures, mitral valve surgery, and trans-catheter interventional procedures [2,[7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Augmented or mixed reality, in fact, accounting for head-sets made of translucent glasses, allows for real-time rendering of holographic 3D contents in the surrounding world, while preserving the interaction with the actual environment [1]. This technology is currently used for education, simulation, and procedural planning in the surgical and/or trans-catheter treatment of patients with congenital and acquired heart disease [2][3][4][5][6][7][8][9][10], but still presents some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, poor radiologic scans require manual reprocessing in contrast to cases with high-quality radiologic scans [ 39 ]. To improve visualization, voxel regions can be assigned specific color and opacity values, or supporting parameters such as textures or annotations can be used to mark or graphically represent structures [ 40 , 41 ]. By transmitting the processed treatment plans over a wireless network to a head-mounted MR device with the appropriate viewer software (Magic Leap 1, Plantation, Florida, USA; Viewer version 5.3, Brainlab AG, Munich, Germany), it is possible to view the radiological data as well as their reconstructions as 3D holograms (see Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%